A efetividade da ação revisional bancária com base no superendividamento - Silva, Gabriel Scherer da (Universidade do Vale do Rio dos Sinos, 2020)
This study has as main objective to evaluate the effectiveness of the institute of judicial review of contracts, in view of bank credit supply contracts as a basis for mitigating the effects of consumer over-indebtedness. In first moment, this work will conceptualize over-indebtedness and demonstrate the profile of the indebted consumer. In any case, as a logical corollary of this phenomenon, the facilitation of credit and it’s consequences. However, it is not intended here to criticize the credit system, but to identify the consequences of its misuse, extending the analysis not only to the less economically privileged classes, but for all those who many times have self submitted abusive legal deals. In a second moment, it will be looking for the reasoning of the bank review action as a form of consumer protection and its obstacles in face of the new systematic perspective of the Civil Procedure Code. Ultimately, it will provide a reflection about the requirement of excessive burdens of the Consumer Protection Code and its repercussion on the over-indebted consumer. The study methodology used will be based on law, doctrine and jurisprudence, as well as empirical study of emblematic cases.
Keywords: Ação revisional; Superendividamento; Direito do consumidor; Contratos de crédito; Revisional action; Over-indebtedness; Consumer law; Credit agreements